Functional Outcomes in Tibial Fractures, Treated by Interlocking Intramedullary Nails Versus Minimally Invasive Percutaneous Plate Osteosynthesis, with Reference to Wound Infections as Complication Rate - Muhammad Imran Butt, Shahzad Anjum, Tayyab Ahmad, Tooba Iqbal, Muhammad Imran Butt, Shahzad Anjum, Tayyab Ahmad, Tooba Iqbal (Journal of Rawalpindi Medical College, 2018)
Background: To compare interlocking intramedullary nails vs minimally invasive percutaneous plate osteosynthesis with locking compression plates for the treatment of diaphyseal tibial fractures, in terms of good functional outcome with reference to wound infections as rate of complications. Methods: In this descriptive study, 140 patients with diaphyseal tibia fractures, were included. The patients included were adults with closed tibial shaft fractures which were less than 2 weeks old, located at 7 cm below the knee joint and 7 cm above the ankle joint. Fractures which were open and of pathological nature were not included in our study. Random allocation into two equal groups was done and 70 patients in group 1 were operated with interlocking nail and remaining 70 in group 2 were operated with Minimally Invasive Percutaneous Plate Osteosynthesis (MIPPO) with a locking compression plate. Follow up of all patients was done uptil 6 weeks. Results: Among all the patients included in the study right tibial fracture involvement was found in 57.9% and that of left side was found in 42.1%. Lesser complications in terms of implant irritation, pain and infection (superficial and deep) were seen in MIPPO group (4.3%) as compared to interlocking group (10%). Conclusion: Due to less infection, less irritability, early union of the fracture and decreased implant related problems, minimally invasive percutaneous plate osteosynthesis, with locking compression plate is preferable in the treatment of tibial shaft fractures over the closed intramedullary interlocking nailing technique.